2020
DOI: 10.1111/1468-2427.12980
|View full text |Cite
|
Sign up to set email alerts
|

Remaking Shanghai: New Divisions in an Expanding Metropolis

Abstract: This study of Shanghai analyzes the city's emerging patterns of residential settlement in 2010. Most previous research on China focused on central city patterns, but by 2010 urban development in major metropolitan areas was taking place predominantly in the suburbs. The analysis re‐examines and extends previous studies of the level of segregation by various key population characteristics, showing that the highest segregation is found in the suburban ring, where original villager residents are now joined by an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Although institutional reforms allow for housing choice to become a factor, existing and strong cultural ties within the work unit will result in the clustering of employees’ homes. This expands on previous research that infers expansion and housing choice with the direct association of the work unit (Gu et al, 2021; Phelps et al, 2021). Such practices are more explicit when contrasting ZhongXin with the neighbouring steel pipe manufacturer work unit (a state-owned enterprise unit), which due to its profitability had explicitly expanded its own territory and contracted developers to build more housing stock beside its area of operation – for its own mainstream employees.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Although institutional reforms allow for housing choice to become a factor, existing and strong cultural ties within the work unit will result in the clustering of employees’ homes. This expands on previous research that infers expansion and housing choice with the direct association of the work unit (Gu et al, 2021; Phelps et al, 2021). Such practices are more explicit when contrasting ZhongXin with the neighbouring steel pipe manufacturer work unit (a state-owned enterprise unit), which due to its profitability had explicitly expanded its own territory and contracted developers to build more housing stock beside its area of operation – for its own mainstream employees.…”
Section: Discussionsupporting
confidence: 71%
“…With capital generated by the housing provident fund and increased salaries, most senior staff (who bought work unit property through housing reform) now live in neighbouring commercial estates ( xiaoqu ) that offer better-quality housing and living conditions. Some of them even own multiple properties, symbolising economic divisions as dependent on when housing was obtained and the concurrent ability to accumulate (see Gu et al, 2021). In 2007 and 2009, the hospital organised group-purchasing ( tuangou ) in neighbouring residential estates.…”
Section: Housing and Residencementioning
confidence: 99%
See 1 more Smart Citation
“…The rapid suburbanization is driven by the abolishment of the welfare housing system, allowing people to choose where they live, and the rise of consumer culture that inspires people to meet their demands for better living conditions (Shen & Wu, 2013). It is also promoted by district and sub‐district governments in the suburbs who heavily rely on land revenues to support local services, and subsequently increased investment in housing and infrastructure construction (Gu et al., 2021).…”
Section: Mechanisms Producing the Socio‐spatial Structure Of Contempo...mentioning
confidence: 99%
“…Answers to these questions also have important societal implications for the establishment of China's 'Harmonious Society' and the 'New Urbanisation Plan', both of which aim for the urban incorporation of domestic rural migrants. 2 Research has shown that neighbourhood-level segregation between migrants and locals in Shanghai was higher in the suburb than in the city centre in both 2000 and 2010 (Gu et al, 2021;Shen & Xiao, 2020). Yet, this might be a specific observation in a single, highly developed city.…”
Section: Introductionmentioning
confidence: 99%